2003
DOI: 10.1161/01.cir.0000105765.54573.60
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Inhibition Alters the Fibrinolytic Response to Cardiopulmonary Bypass

Abstract: Background-Increased plasminogen activator inhibitor-1 (PAI-1) concentrations after coronary artery bypass grafting (CABG) are associated with increased risk of vein graft occlusion. Because angiotensin II stimulates PAI-1 expression, we tested the hypothesis that preoperative angiotensin-converting enzyme (ACE) inhibition decreases PAI-1 expression after CABG. Methods and Results-We measured the effects of cardiopulmonary bypass (CPB) on PAI-1 antigen and tissue-type plasminogen activator (tPA) antigen and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 44 publications
5
25
2
Order By: Relevance
“…19 PAI-1 antigen concentrations transiently decrease during CPB and then begin to rise by separation from CPB, peaking on postoperative day 1. 9,20 On the other hand, we found that preoperative PAI-1 concentrations predicted postoperative AF suggesting that the underlying inflammatory and profibrotic state rather than the acute inflammatory response, may determine risk of this event. Moreover, the selection of the postprotamine time point enabled us to assay blood when many biomarkers are starting to rise, but early enough to direct future preventive strategies.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…19 PAI-1 antigen concentrations transiently decrease during CPB and then begin to rise by separation from CPB, peaking on postoperative day 1. 9,20 On the other hand, we found that preoperative PAI-1 concentrations predicted postoperative AF suggesting that the underlying inflammatory and profibrotic state rather than the acute inflammatory response, may determine risk of this event. Moreover, the selection of the postprotamine time point enabled us to assay blood when many biomarkers are starting to rise, but early enough to direct future preventive strategies.…”
Section: Discussionmentioning
confidence: 73%
“…30,31 In a study of patients treated preoperatively with an ACE inhibitor and randomized to continue or discontinue ACE inhibition, continued ACE inhibition decreased plasma PAI-1 antigen concentrations after CPB. 20 …”
Section: Discussionmentioning
confidence: 99%
“…(31) In two small randomized trials in chronic ACE inhibitor users, postoperative PAI-1 concentrations were lower in patients continued on ACE inhibitor therapy compared to in patients whose ACE inhibitor was stopped prior to cardiac surgery. (13, 32) MR antagonists also reduce inflammatory cytokines and PAI-1 in normotensive or hypertensive subjects. (33, 34) In the present clinical trial, we observed the previously reported association between the inflammatory response to cardiac surgery and postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…ACE inhibitors attenuate the inflammatory response to cardiac surgery and specifically reduce plasma concentrations of inflammatory biomarkers associated with the development of postoperative AF. (12, 13) Conversely, ACE inhibitor withdrawal is associated with postoperative AF. (3) Nevertheless, many physicians withhold ACE inhibitors in the perioperative period due to concerns about perioperative hypotension and impaired kidney function.…”
mentioning
confidence: 99%
“…This change may be due to improving endothelial cell function, PAI-1 antigen attenuation (thus reducing thrombosis), or due to a decrease in matrix metalloproteinase production and matrix remodelling (thus limiting SMC migration) and SMC proliferation [225].…”
Section: Antiproliferative and Antimigrating Agentsmentioning
confidence: 99%